IMPACT OF VAT AND CORPORATE INCOME TAX POLICY TO STOCK PRICES ON CONSUMER CYCLICALS SUB-SECTOR LISTED ON INDONESIA STOCK EXCHANGE - Martha Martha; Arie Kozona Sembiring; Teddy Chandra; Agus Hocky (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
This research examines the impact how changes in Value-Added Tax (VAT) and Corporate Income Tax (CIT) policy affect to stock prices on consumer cyclicals sub-sector listed on Indonesia Stock Exchange. By applying an event study methodology, the research evaluates how investors reacted to four key fiscal policy events such as (1) Determination and Enforcement of Government Regulation in Lieu of Law No. 1 of 2020 (corporate income tax rate reduced from 25% to 22%) on March 31, 2020; (2) Ratification of Law No. 7 of 2020 (VAT rate increased from 10% to 11%, and corporate income tax remained at 22%) on October 29, 2021; (3) Enforcement of Law No. 7 of 2020 (VAT rate increased from 10% to 11%) on April 1, 2022; and (4) Issuance of Minister of Finance Regulation No. 131 of 2024 (VAT rate remained at 11%) on December 31, 2024. The analysis uses daily stock price and trading volume data from 20 selected companies. Data analysis technique used Paired Sample t-Test and Wilcoxon Signed Rank Test to assess the presence of abnormal returns and changes in trading volume activity (TVA) before and after the events. Research findings indicate that certain tax policy changes triggered significant responses in the capital market, reflecting shifts in investor sentiment and decision-making. These insights are valuable not only for policymakers in evaluating the market impact of taxation but also for company managers and investors seeking to anticipate market behavior in response to regulatory changes. Penelitian ini bertujuan untuk menganalisis dampak kebijakan tarif Pajak Pertambahan Nilai (PPN) dan Pajak Penghasilan Badan (PPh Badan) terhadap harga saham perusahaan sub sektor Consumer Cyclicals yang terdaftar di Bursa Efek Indonesia (BEI). Metode penelitian yang digunakan adalah event study dengan menganalisis abnormal return dan trading volume activity (TVA) pada empat peristiwa perubahan kebijakan perpajakan yakni (1) Penetapan dan Penyelenggaraan Peraturan Pemerintah Pengganti Undang-Undang No. 1 Tahun 2020 (tarif pajak penghasilan badan dikurangi dari 25% menjadi 22%) pada 31 Maret 2020; (2) Pengesahan Undang-Undang No. 7 Tahun 2020 (tarif PPN dinaikkan dari 10% menjadi 11%, dan pajak penghasilan badan tetap 22%) pada 29 Oktober 2021; (3) Penyelenggaraan Undang-Undang No. 7 Tahun 2020 (tarif PPN dinaikkan dari 10% menjadi 11%) pada 1 April 2022; dan (4) Dikeluarkannya Peraturan Menteri Keuangan No. 131 Tahun 2024 (tarif PPN tetap 11%) pada 31 Desember 2024. Hasil penelitian menunjukkan bahwa perubahan tarif PPh Badan dan PPN berpengaruh signifikan terhadap harga saham dan aktivitas perdagangan saham. Penurunan tarif PPh Badan memberikan sinyal positif bagi pasar, sedangkan kenaikan tarif PPN cenderung direspons negatif oleh investor. Temuan ini memberikan implikasi bagi investor, manajemen perusahaan, dan pembuat kebijakan dalam mengambil keputusan strategis terkait kebijakan perpajakan.